Industrially Purified Nd Materials Identified by Distinct Mass-Dependent Isotopic Composition - Bothamy, Nina; Galy, Albert (Frontiers in Environmental Chemistry, 2021)
Since few decades, rare earth elements (REEs) are considered as emerging pollutant. Anthropogenic lanthanum, samarium and gadolinium have already been reported in natural waters. And it is only a matter of time for neodymium (Nd) of anthropogenic origin to be reported in the environment, given its growing demand for new technologies and permanent magnets. Nd concentration in soils and sediments is high enough to prevent the discrimination of anthropogenic from natural Nd. For this reason, we propose the use of the Nd stable isotopic composition, expressed as δxNd, the relative permil (‰) deviation from the isotopic composition of the pure Nd JNdi-1 reference standard, to help their distinction. The measurement of δxNd used a MC-ICPMS (Multi-Collector Inductively Coupled Plasma Mass Spectrometry) with sample-standard bracketing technique, allowing the determination of precise and accurate Nd isotopic variations. Our results show that Nd-magnets (Neo) and man-made purified Nd materials are not significantly different in average (respectively δ148Nd of -0.105 ± 0.023 and -0.120 ± 0.141‰). More importantly, they are different from terrestrial rocks (δ148Nd of -0.051 ± 0.031‰). In addition, the study of all Nd stable isotopic compositions demonstrates that irrespective of their origin (or radiogenic composition) all Nd from rocks and man-made materials are related by mass-dependent isotopic fractionation laws. However, a small deficit in 150Nd (around 5 ppm/‰/amu) is observed for anthropic materials, too small to be consistent with nuclear field effect, but in full agreement with the theoretical expectation from mass-dependent kinetic isotopic fractionation. The mass-dependent fractionation of Nd by chromatographic separation is also consistent with a kinetic isotopic fractionation. The purification of Nd from other light REEs by industrial processes involves chromatographic separation and, therefore, is likely to produce anthropic Nd enriched in light isotopes, associated with a small deficit in 150Nd. Both are resolvable with current MC-ICPMS technology and could be useful to trace incoming anthropogenic pollution in the environment.